ANALYSIS STUDY ON THE IMPLEMENTATION OF ISLAMIC EDUCATION RECONSTRUCTION BASED ON MULTYDICIPLINARY STUDY IN EAST JAVA ISLAMIC BOARDING SCHOOL COLLEGE - Evita Yuliatul Wahidah; Agus Salim (LPPM STAI Muhammadiyah Probolinggo, 2020)
The change or inovation in Indonesia Islamic education is related with recontstruction idea which influences scientific progress in education environment including Islamic Boarding School. Reconstruction idea has found its momentum since the beginning of 20th century, while in the education field was transformed into the establishment of modern educational institutes. College in the Islamic boarding schools that spread among East Java are one of many colleges in the Islamic boarding school which can not avoid from reconstruction that has run through all over regions.The research aim is finding out the background of implementation form, also the input and output reality of Islamic education reconstruction base on Islamic boarding school college multydiciplinary in East Java. It is a discriptive qualitative reasearch with etnographic approach. The methods of data collection are participant observation, interview, and documenter method.Base on the research, it is identified that the Islamic boarding school colleges in East Java are independent college which have shown their strength by building scientific pillars that cover all of part in science, both general and relegion, with the base of multydiciplinary learning. Islamic education, from time to time, has conducted recostruction on its system and management by holding on college tridarma, which are education, research and community service.